Urea Crystallization Optimization of Oil from Lemuru (Sardinella longiceps) Meal Processing by Product for Concentrate ω-3 Fatty Acids Preparation - Estiasih, Teti (Jurnal Teknologi Pertanian, 2010)
Oil from lemuru meal processing by product is a potential and an abundant source of ω-3 fatty acids. This oil can be processed to be ω-3 fatty acids concentrate. Urea crystallization is a method for producing high content of ω-3 fatty acids concentrate. Production of ω-3 fatty acids concentrate from lemuru oil was optimized. Central composite design of response surface method was employed as experimental design with two variables, urea-to-fatty acids ratio and crystallization time toward response of EPA+DHA content. The result showed that quadratic regression model was suitable to explain the interaction between both variables toward response of EPA+DHA content whereas urea-to-fatty acids ratio was optimum at 2.59:1 and crystallization time was optimum at 24 hours 18 minute. EPA+DHA content of ω-3 fatty acids concentrate in optimum condition was verified and showed the value was 57.90%, recovery yield was 34.7%, which was increased 2.51 times compared to original lemuru fish oil. Optimum ω-3 fatty acids concentrate quality met the International Association of Fish Meal Manufacturer (IFOMA) standard except for copper concentration.Keywords: optimization, oil from lemuru meal processing by product, urea crystallization, EPA+ DHA content